DIGITALIZATION OF RESOURCE MANAGEMENT IN CALIBRATION LABORATORIES AND DEVELOPMENT OF AN INTEGRATED IMPACT ASSESSMENT METHODOLOGY - Patidinov Nurillo Turgunbaevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The transformation of calibration laboratories into digitally managed, efficiently resourced entities represents a new era in technical service provision. This article explores the digitalization process in the context of resource management for calibration laboratories, with a particular focus on the creation of a methodology that enables comprehensive, integrated evaluation of how digitized resource management influences laboratory performance, compliance, quality, and sustainability. The work draws on current trends, practical laboratory realities, and international standards, proposing grounded solutions for laboratory professionals and managers.